Are Consumer Rights Human Rights: The Intersection of Consumer Rights and Human Rights: A Comprehensive Analysis (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Since World War II, consumer protection has been increasingly important. In a similar vein, theidea of human rights has gained popularity. The claim that the propensity to widen the concept of humanrights permits us to incorporate consumer rights within that definition is supported by substantive andprocedural assessments of human rights. In a culture that values consumption, safeguarding the interestsof the individual consumer is seen as an important component of upholding human dignity, particularly inthe face of powerful cartels, monopolies, and multinational companies. Therefore, the basis forrecognising consumer rights as human rights may be found in widely recognised human rightsprinciples, such as the focus placed on an individual's prosperity, honour, and dignity.